HATA PANGUPA: SASTRA LISAN MANDAILING DI KOTANOPAN SETIA NAGARI LANSEK KADOK KECAMATAN RAO SELATAN KABUPATEN PASAMAN - Desti, Fefa Srila; Krisna, Eva; Muhardis, Muhardis (Pendidikan Bahasa Indonesia, 2013)
This research is motivated from one effort to maintain and preserve Hata Pangupa part of oral literature Mandailing, especially in Kotanopan Setia Kampong, Nagari Lansek Kadok, Kecamatan Rao SelatanÂ  Kabupaten Pasaman. Discussion of this research is Hata Pangupa in the Upa - Upa the wedding ceremony. Some research results on Hata Pangupa at the wedding ceremony, namely: ( 1 ) the context of oral literature Hata Pangupa spoken in Kotanopan Setia Kampong, Nagari Lansek Kadok, Kecamatan Rao Selatan, Kabupaten Pasaman. Elements of the show, the speakers, ritual instruments, place and time of the narrative, atmosphere and management of the wedding ceremony, as well as the Upa - Upa wedding participants; (2 ) the form of a long poem in the form of text edits are accompanied by translations; (3) HataPangupa as along poem with the characteristics, namely: priority to the use of language rhythm, similar sound repetitive or have poetry, as well as repeat a picture with various similar parables, and (4) function Hata Pangupa in Kotanopan Setia Kampong, namely: didaktif function, aesthetic function, the function of moral, and religious functions, as well as teaching values contained in Hata Pangupa, namely: obedience to God, obedience to parents and customs regulations, settle down and get along in society, always doing good, going to work, having responsibilities, and likes to work together and helping each other.